Profil Perilaku Agresif Siswa dan Implikasinya bagi Bimbingan Konseling - Dita Kurnia Sari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Aggressive behavior is an act of violence that harm, hurt, injure because it will harm the victim that was done on purpose in the form of active or passive, physically or verbally either in person or not. The purpose of this study was to determine the profile of aggressive behavior class XI SMA Laboratorium UM Malang. The method used in this research is descriptive analysis. The results showed that (1) the level of aggressive behavior in class XI SMA Laboratorium UM Malang high, (2) the level of aggressive behavior of male students are higher than female students, (3) the form of aggressive behavior of male students more patterns of behavior physically aggressive, active and direct, (4) the form of aggressive behavior more female students in the form of verbal aggressive behavior, passive and indirect.